Strategic Financial Management: Understanding the Dynamics of Financial Strategy, Performance and Investment Decisions - Adi, Anas Firman (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
This research aims to delve into the intricacies of strategic financial management, performance evaluation, and investment decision-making processes within organizations. Employing a qualitative analysis and comprehensive literature review, the study explores various dimensions of these critical areas to uncover valuable insights. The research underscores the multifaceted nature of financial strategy dynamics, emphasizing the importance of aligning financial strategies with broader organizational goals, considering risk tolerance, cost of capital, and market dynamics. Moreover, it highlights the evolving nature of financial strategies in response to industry trends, technological advancements, and regulatory requirements. Performance evaluation dynamics are examined, advocating for a holistic approach that comprehensively integrates financial and non-financial indicators to assess organizational performance. Investment decision-making processes are also scrutinized, focusing on the need for organizations to adopt flexible and adaptive strategies amidst globalization, technological disruption, and changing consumer preferences. The findings underscore the significance of strategic alignment, innovation, and risk management in driving organizational success and sustainability. Overall, this research contributes to a deeper understanding of strategic financial management practices and provides valuable insights for organizational decision-makers.